Analysis of mathematical communication ability on prospective elementary school teachers based on self-regulated learning level - Ristiana, Muhammad Ghiyats; Wahyudin, Wahyudin; Herman, Tatang; Nurjanah, Nurjanah (IKIP Siliwangi and I-MES, 2025)
Mathematical communication skills are essential for prospective elementary school teachers. However, many problems still occur in prospective elementary school teachers related to their mathematical communication skills. This study aims to describe the mathematical communication skills of prospective elementary school teachers and their level of self-regulated learning. This qualitative research, employing a phenomenological design, aims to explore and identify the mathematical communication skills of prospective elementary school teachers. Forty-eight prospective elementary school teachers participated in this study, and nine were selected for in-depth interviews to understand their mathematical communication skills better. The results showed that prospective elementary school teachers with high self-regulated learning almost met all indicators, prospective teachers with moderate self-regulated learning met three indicators, and prospective teachers with low self-regulated learning met one indicator. All of them were unable to provide mathematical solutions with rational reasons. Several factors cause prospective elementary school teachers not to have good mathematical communication skills, such as 1) lack of knowledge of basic geometry concepts, 2) lack of motivation to learn independently, 3) inability to manage what to learn, and 4) inability to evaluate their mistakes. Based on the research results, not all prospective elementary school teachers possess practical communication skills.